Assessing the Chemistry and Bioavailability of Dissolved Organic Matter From Glaciers and Rock Glaciers. Issue 7 (11th July 2019) - Fegel, Timothy; Boot, Claudia M.; Broeckling, Corey D.; Baron, Jill S.; Hall, Ed K.
Abstract: As glaciers thaw in response to warming, they release dissolved organic matter (DOM) to alpine lakes and streams. The United States contains an abundance of both alpine glaciers and rock glaciers. Differences in DOM composition and bioavailability between glacier types, like rock and ice glaciers, remain undefined. To assess differences in glacier and rock glacier DOM we evaluated bioavailability and molecular composition of DOM from four alpine catchments each with a glacier and a rock glacier at their headwaters. We assessed bioavailability of DOM by incubating each DOM source with a common microbial community and evaluated chemical characteristics of DOM before and after incubation using untargeted gas chromatography–mass spectrometry‐based metabolomics. Prior to incubations, ice glacier and rock glacier DOM had similar C:N ratios and chemical diversity, but differences in DOM composition. Incubations with a common microbial community showed that DOM from ice glacier meltwaters contained a higher proportion of bioavailable DOM and resulted in greater bacterial growth efficiency. After incubation, DOM composition from each source was statistically indistinguishable. This study provides an example of how MS‐based metabolomics can be used to assess effects of DOM composition on differences in bioavailability of DOM. Furthermore, it illustrates the importance of microbial metabolism in structuring composition of DOM. Even though rock glaciers had significantly less bioavailable DOM than ice glaciers, both glacial types still have potential to be important sources of bioavailable DOM to alpine headwaters over the coming decades. Key Points: Both glaciers and rock glaciers supply highly bioavailable sources of organic matter to alpine headwaters in Colorado Bioavailability of organic matter released from glaciers is greater than that of rock glaciers in the Rocky Mountains The use of GC‐MS for ecosystem metabolomics represents a novel approach for examining complex organic matter pools